Acute histological reactions in the otolith organs to inner ear drug delivery through a cochlear implant - Manrique-Huarte, Raquel; Álvarez de Linera-Alperi, Marta; Pérez-Fernández, Nicolás; Manrique, Manuel (Frontiers in Neurology, 2024)
A significant concern is the safety of cochlear implantation with regard to vestibular preservation and hearing. New advances in electrode arrays, such as CI devices associated with delivery pumps, pose a challenge in maintaining minimally traumatic surgical concept-based procedures without altering the inner ear homeostasis. The implantation of this device may cause vestibular hydrops in the saccule. Suggesting that the longer the time of substance release, the greater the hydrops evidenced at the saccular level. Apart from this finding, the risk of histological damage to the vestibule is low.